Comparing 0.75% Ropivacaine and 0.5% Levobupivacaine For Peribulbar Blockade In Vitrectomy Surgery Towards Intraocular Pressure - Doddy Tavianto; Ricky Aditya; Dian Irawati; Aria Annasya (International Journal Labs, 2024)
Peribulbar blockade is a regional anesthetic technique that can be used for vitrectomy surgery. Ropivacaine and levobupivacaine are local anesthetics that have the advantage of a long duration of action and a lower complication rate than bupivacaine. This study aims to find the effect of intraocular pressure from ropivacaine and levobupivacaine. The study design was a double-blind randomized controlled trial on 60 patients underwent vitrectomy at Netra Ophthalmic Clinic Bandung with peribulbar blockade. Twenty-nine subjects received 0.75% ropivacaine and thirty-one subjects received 0.5% levobupivacaine for peribulbar blockade. Assessment of eye intraocular pressure was assessed before the block, 5 minutes, 10 minutes, and 15 minutes. The 0.75% ropivacaine group obtained an average of 4.42mmHg at 15 minutes, while the 0.5% levobupivacaine group averaged 2.33mmHg after 15 minutes after injection. Statistical results obtained p value <0.05 which means significant intraocular pressure of the two drugs. Intraocular pressure of ropivacaine 0.75% lower than levobupivacaine 0.5% in peribulbar blockade in vitrectomy surgery.